Design Thinking Implementation for User Experience Improvement of UNS Graduation Website: A Case Study - Tamma, Ghani Naufal; Iftadi, Irwan; Astuti, Rahmaniyah Dwi (TALENTA Publisher, 2025)
Design thinking is a human-centered problem-solving methodology focusing on innovative solutions. Design thinking can be used to improve the user experience of a website. Design thinking consists of empathize, define, ideate, prototype, and test phase. Based on preliminary observation, the current UNS Graduation Website demonstrates significant usability issues that interrupt the user experience. The lack of error prevention and informative feedback leads to repeated mistakes and user frustration. Additionally, visual and functional inconsistencies further reduce usability. These issues were confirmed through the System Usability Scale (SUS), which yielded a low score, indicating a difficult and unpleasant user experience. To address these issues, this study applies the design thinking methodology to re-design the UNS Graduation Website with the aim of improving its usability and enhancing user experience. The prototype is tested by 20 users using usability testing tools named Maze and System Usability Scale (SUS). The result based on Maze testing, the prototype got a success rate percentage of 100% and a usability score of 85 for the UNS Graduation Website. The usability score tested by SUS also increased from 43,25 to 82. This affirms the successful outcome of the re-design in improving the user experience and increasing the usability of the UNS Graduation Website.